2008
DOI: 10.1002/jbm.a.32289
|View full text |Cite
|
Sign up to set email alerts
|

Injectable cell‐free template for bone‐tissue formation

Abstract: Here we present a novel injectable hydrogel which forms a template for de novo formation of bone tissue. Hydrogel formation takes place in situ in less than 1 min by the cross-linking of multifunctional hyaluronic acid and polyvinyl alcohol derivatives. Endogenous cells are recruited in vivo by incorporating bone morphogenetic protein-2 (BMP-2), a powerful promoter for osteogenic differentiation. The hydrogel was evaluated in vitro by performing a cell viability test and a release study and in vivo by a rat ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 37 publications
4
88
0
1
Order By: Relevance
“…Previous studies have demonstrated that modified alginate and hyaluronic acid hydrogels induce bone formation in vitro [8,14,15,17,26,36,37] and in vivo [15,17,19,27]. Here, we demonstrate that unmodified hydrogels also support osteoblast differentiation, though alginate hydrogels induced a higher degree of differentiation than the high molecular weight hyaluronic acid hydrogels used in the present study.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Previous studies have demonstrated that modified alginate and hyaluronic acid hydrogels induce bone formation in vitro [8,14,15,17,26,36,37] and in vivo [15,17,19,27]. Here, we demonstrate that unmodified hydrogels also support osteoblast differentiation, though alginate hydrogels induced a higher degree of differentiation than the high molecular weight hyaluronic acid hydrogels used in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, when containing bFGF, HA hydrogels enhance calcium deposition, osteopontin and BSP expression and decrease alkaline phosphatase in rat bone marrow stromal cells [26]. In vivo, HA hydrogels containing BMP-2 showed increased bone formation [19,27].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hydrogels, such as fibrin, hyaluronic acid and Pluronic F127, have shown promising result for effective growth factor delivery 56 . As reported by Dhillon et al, 57 blending PLGA with a plasticizer, such as polyethylene glycol (PEG), allows the production of temperature-sensitive material with a reduced Tg of 37 °C.…”
Section: C) Hydrogelsmentioning
confidence: 99%
“…Furthermore, it has been shown that the opening of sugar rings by periodate oxidation results in a HA derivative that lacks its cellular recognition properties [80]. Varghese et al proposed a simple and versatile synthetic strategy to graft aldehyde moieties on HA without compromising the structural integrity of the polymer [81].…”
Section: Ha-protein Conjugatesmentioning
confidence: 99%